Electrochemical Characterization of Synthetic Hybrid DNA Molecular Wires. (25th April 2016) - Golkar Narenji, Alaleh; Goshi, Noah; Coste, Michael; Burns, Dillon; Lee, Raymond; Ngo, Katrina; Purse, Byron; Kassegne, Sam
Abstract : As a viable solution to long-term stability problems associate with DNA molecular wires along with the additional benefits of tuning their conductivity, hybrid DNA molecular wires made of natural base-pairs and synthetic base-pairs, which have lower ionization potentials and a more π orbital overlapping, offer an attractive option. A strong synthetic nucleotide candidate is tricyclic cytosine analogue (such as (8-MeO)tC), which we show has (i) a lower ionization potential ( 0.65V) compared to natural nucleotides, G (1.29V), C (1.6V), A (1.42V), T (1.7V) and (ii) more π-orbital stacking due to its tricyclic structure. Moreover, to illuminate the importance of the π orbital stack to the conductivity of DNA molecular wires, in this paper, we compared the conductivity of wild-type (WT) DNA and DNA sequences containing mismatched base-pairs that perturb the π orbital stack. Lower conductivity was obtained when modifying the surface of the gold electrodes with both WT and mismatched DNA. Further, chips functionalized with DNA sequences with mismatched base-pairs were observed to have lower conductivity than those functionalized with WT DNA sequences.